Financialization in Kaleckian Economies with and without Labor Constraints - Soon Ryoo; Peter Skott (Intervention. European Journal of Economics and Economic Policies, 2008)
Most Kaleckian models assume a perfectly elastic labor supply, an assumption that is questionable for many developed economies. This paper presents simple labor-constrained Kaleckian models and uses these models to compare the implications of financialization under labor-constrained and dual-economy conditions. The paper complements the analysis in Skott and Ryoo (2008) which did not include labor-constrained Kaleckian economies. We show that for plausible parameter values the financial changes commonly associated with financialization tend to be expansionary in both dual-economy and labor-constrained settings.
Keywords: E12; E44; 330; financialization; stock-flow consistency; labor constraints; Kaleckian model